Interactions Between Poly(N-vinyl pyrrolidone) and Sodium Dodecyl Benzene Sulfonate in Aqueous Solution - Chen, Xiaoming (Asian Journal of Chemistry, 2014)
Poly(N-vinyl pyrrolidone) is a nonionic water-soluble amphiphilic polymer. The nitrogen atom of side group in poly(N-vinyl pyrrolidone) macromolecular chain possesses a partial positive charge. Therefore, electrostatic interactions between the nitrogen atom in poly(N-vinyl pyrrolidone) and the anionic surfactant headgroup of sodium dodecyl benzene sulfonate should be taken into account in PVP-SDBS system. As a result the viscosity, conductivity and surface tension measurements show that the interaction between poly(N-vinyl pyrrolidone) and sodium dodecyl benzene sulfonate can be explained by the two-stages interaction model which orignally is suggested for polyelectrolyte-surfactant systems. In the first stage the anionic headgroups of sodium dodecyl benzene sulfonate individually bind to the "cationic" side groups of poly(N-vinyl pyrrolidone) chain due to electrostatic attraction. When the surfactant concentration increases, the second stage of the micellization of polymer-bound surfactant occurs.